Planobispora takensis sp. nov., isolated from soil - Wipaporn Ngaemthao; Chanwit Suriyachadkun; Suwanee Chunhametha; Nantawan Niemhom; Chitti Thawai; Jean-Jacques Sanglier (My University, 2014)
A novel Gram-stain-positive, filamentous bacterial strain (A-T 7458(T)) was isolated from soil collected from hill evergreen forest in Thailand. The strain developed cylindrical sporangia containing a longitudinal pair of motile spores, on short ramifications of aerial mycelia. From a taxonomic study using a polyphasic approach, strain A-T 7458(T) had typical characteristics of members of the genus Planobispora. 16S rRNA gene sequence analysis indicated that the isolate was closely related to Planobispora siamensis A-T 4600(T) (98.5 %), Planobispora rosea JCM 3166(T) (97.6 %) and Planobispora longispora NBRC 13918(T) (97.6 %). The DNA-DNA relatedness values, which differentiated the novel strain from the closest species, were significantly below 70 %. The cell-wall peptidoglycan contained meso-diaminopimelic acid. The whole-cell sugars contained ribose, madurose, mannose and glucose. The predominant menaquinone was MK-9(H2). The diagnostic phospholipids were diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, phosphatidylmethylethanolamine, phosphatidylinositol, phosphatidylinositol-mannoside and aminophosphoglycolipid. The predominant cellular fatty acids were unsaturated C17 : 1 and C18 : 1, and saturated C16 : 0 and C17 : 0. Following an evaluation of phenotypic, chemotaxonomic and genotypic characteristics, the novel isolate is proposed to represent a novel species of the genus Planobispora, to be named Planobispora takensis sp. nov. The type strain is A-T 7458(T) ( = BCC 48396(T) = NBRC 109077(T)).
Keywords: Strain (injury); Diamino acid; Diaminopimelic acid; Genomics and Phylogenetic Studies